Computational Analysis of Pathological Image Enables Interpretable Prediction for Microsatellite Instability - Zhu, Jin; Wu, Wangwei; Zhang, Yuting; Lin, Shiyun; Jiang, Yukang; Liu, Ruixian; Zhang, Heping; Wang, Xueqin (Frontiers in Oncology, 2022)
Microsatellite instability (MSI) is associated with several tumor types and has become increasingly vital in guiding patient treatment decisions; however, reasonably distinguishing MSI from its counterpart is challenging in clinical practice. In this study, interpretable pathological image analysis strategies are established to help medical experts to identify MSI. The strategies only require ubiquitous Haematoxylin and eosin-stained whole-slide images, and perform well in the three cohorts collected from The Cancer Genome Atlas. Equipped with machine learning and image processing technique, intelligent models are established to diagnose MSI based on pathological images, providing the rationale of the decision in both image-level and pathological-feature-level. The strategies achieve two levels of interpretability. First, the image-level interpretability is achieved by generating localization heat maps of important regions based on deep learning. Second, the feature-level interpretability is attained through feature importance and pathological feature interaction analysis. Interestingly, from both the image-level and feature-level interpretability, color and texture characteristics, as well as their interaction, are shown to be mostly contributed to the MSI prediction.